Меры по предупреждению хрупких разрушений роторов. Требования к характеристикам металлов - Сухинин, В. П.; Пугачева, Татьяна Николаевна (НТУ "ХПИ", 2010)
The issues has been treated connected o fdestruction of rotors. The criteria of determination of strongly descriptions at which passingof material of rotor is possible to the fragile state and his destruction are offered, that is related to inflexibility of the tense state
Keywords: роторы паровых турбин; турбоагрегаты; виды разрушений